Practices and challenges of implementing early childhood care and education in Bahir Dar city administration, Ethiopia - Asmamaw Ashete Wendie; Kelemu Zelalem Berhanu (International Journal of Child Care and Education Policy)
Abstract Early childhood care and education (ECCE) is the basis for the enduring instillation of personal habits and societal ideals. Thus, the study aimed to investigate the practice and challenges of implementing ECCE in Bahir Dar city administration, Ethiopia. To this end, a qualitative research approach with a multiple case study design was used. Qualitative data were collected from 40 participants (ECCE teachers, caregivers, unit leaders, school principals, and Bahir Dar city administration education experts). Observation, interviewing, and focus group discussion were used as data collection instruments. As a result, ECCE was poorly implemented. By and large, the finding of this study identified many challenges that inhibit the successful implementation of ECCE, such as lack of teachers and caregivers’ training, poor physical environment, inadequate resources/facilities, inappropriate teacher–student ratio, and unrealistic demands of parents. These hindrances increase learning gaps that widen over time, contributing to higher dropout rates and reduced literacy levels. The study results would have important implications for the advancement of the ECCE program. Additionally, the findings might inform policymakers and educators on areas that require further development or intervention, ultimately contributing to improving of early childhood learning experiences.